2018
DOI: 10.1016/j.bbmt.2018.04.010
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral Blood Grafts for T Cell–Replete Haploidentical Transplantation Increase the Incidence and Severity of Cytokine Release Syndrome

Abstract: T cell-replete post-transplant cyclophosphamide (PTCy)-based protocols have led to increasing use of haploidentical allogeneic hematopoietic cell transplantation (haploHCT). With this approach, bidirectional alloreactivity causing nonengraftment or severe graft-versus-host disease (GVHD) is no a longer major barrier to haploHCT. PTCy eliminates alloreactive lymphocytes but spares CD34 stem cells and regulatory T lymphocytes, resulting in reliable hematopoietic recovery with relatively low incidence of GVHD. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
20
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(22 citation statements)
references
References 31 publications
1
20
1
Order By: Relevance
“…Different studies showed similar results. 6,24 In our analysis in the haplo-HSCT cohort a number of TNC infused greater tan 6x10 8 / kg significantly increased the probability of developing CRS. Concomitantly, the fact that CD34+ cells infused did not correlate with the occurrence of CRS, suggests that T-cell content might play a significant role, since it is the largest cell subset in PBSC mobilized with G-CSF from healthy donors.…”
Section: Discussionmentioning
confidence: 64%
See 2 more Smart Citations
“…Different studies showed similar results. 6,24 In our analysis in the haplo-HSCT cohort a number of TNC infused greater tan 6x10 8 / kg significantly increased the probability of developing CRS. Concomitantly, the fact that CD34+ cells infused did not correlate with the occurrence of CRS, suggests that T-cell content might play a significant role, since it is the largest cell subset in PBSC mobilized with G-CSF from healthy donors.…”
Section: Discussionmentioning
confidence: 64%
“…12,13 In this retrospective study, we with previous autologous transplantation) and also to a different criteria for CRS grading. 6 In another study with a similar transplant platform, Abboud R. et al analyzed CRS in a total of 75 patients. Nine of them had CRS grades 3 to 4, and seven were treated with tocilizumab.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, McCurdy et al [38] reported that CRS occurred in 44% after NMA-based PTCy-haploBMT, and 84% after MAC-based PTCy-haploBMT. Raj et al [39] demonstrated that PBSCT was significantly associated with grade ≥ 2 CRS, compared with BMT. With regard to the risk of CRS, McCurdy et al reported that CRS after PTCy-haploBMT is associated with myeloablation, HLA-class II mismatching, and higher CD3 + graft cell dose.…”
Section: Cytokine Release Syndrome After Ptcy-haplosctmentioning
confidence: 99%
“…The reason for this is that allotransplant specialists will have the greatest experience in the treatment of the potential severe CAR-T cell-induced side effects. 15,16 In the article by Moreau et al in this edition of Haematologica, European Myeloma Network (EMN) experts discuss the future use of CAR-T cell therapies in multiple myeloma patients (by multiple myeloma experts, rather than an allogeneic team) as highly relevant and warranted. 17 The recommendation for specialist care by allogeneic-transplant specialists in CAR-T-cell therapies is, therefore, debated by Moreau et al for myeloma patients, one reason being that centers with leading expertise in myeloma treatment including autologous stem cell transplantation may not necessarily have a unit for allogeneic transplantation.…”
mentioning
confidence: 99%